Rod Migration into the Posterior Cranial Fossa after C1–C2–C3–C4 Screw Fixation: Case Report and Review of the Literature - Igor Vadimovich Basankin; Vladimir Alekseevich Porkhanov; Abram Akopovich Giulzatyan; Pavel Borisovich Nesterenko; Eduard Romanovich Khurshudyan; Marina Igorevna Tomina; Ivan Evgenievich Gritsaev; Karapet Karapetovich Takhmazyan; Sergey Borisovich Malakhov (Indian Journal of Neurosurgery, 2024)
Screw loosening, avulsion, fracture, and rod migration are mechanical complications associated with dorsal fixation of the cervical spine. These usually occur in the late postoperative period and range from 2 to 5%. In this article, we describe a rare case of rod migration into the posterior cranial fossa 4 years after C1–C2–C3–C4 screw fixation in a patient with traumatic fracture of the C2 and C3 vertebrae.